The Influence of Experience on the Farmers’ Attitudes in Utilizing Integrated Rice Agricultural Services Center (SP3T) - Pradite Nimas Ayu Astardiana; Suminah; Sugiharjo (International Journal of Science and Society, 2020)
Farmers need facilities to support agricultural productivity. The government provides agricultural equipment assistance to the success of the program to increase production, productivity and quality of food crops in the form of Integrated Rice Agriculture Service Centers (Sentra Pelayanan Pertanian Padi Terpadu/SP3T). One of the facilities provided in the program to increase the production, productivity and quality of food crops is the SP3T sub-program in which the facilities provided are more focused on post-harvest tools and production facilities. Central Java Province and 33 other provinces were given the opportunity to run the SP3T sub-program. Central Java is a province that has the highest rice production in 2019. This study aims to determine the effect of personal experience on farmers' attitudes in using Integrated SP3T. Sampling was purposive as many as 75 people. The basic method of research is descriptive quantitative. The data used are primary and secondary data. The data analysis used is simple linear regression. The results showed that there was a significant effect (p = 0.001) between personal experience and farmer attitudes.